Assessment Performance of Pumps as Hydro-Turbines - Suarda, Made (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009, 2012)
The basic principle work of hydro-turbines are reversal of pumps, therefore, an alternative solution that can be developed inovercoming problem to get hydro turbines are by using pumps, by flowing water in the reverse direction through in thepumps, as hydro turbines. Those are supported by availability of pumps widely in the market and have been mass-producedhence they were relatively cheap. The aims of this research are to determine performances of pumps as turbines - reversepumps. This experiment assesses performance of two small pumps that are centrifugal ‘diffuser-pump’ and ‘volute-pump’ ashydro turbines with various debit and head of water flow resource, such as output-powers and their efficiencies. The resultsshow that the centrifugal diffuser-pump as hydro turbine performs maximum efficiency about 20,6%, where is as pump fromits brochure suppose 47%. In the other hand, the centrifugal volute-pump as turbine achieves maximum efficiency about32%, where is expected 26% as pump from its brochure. Both type of the pumps present that the maximum efficiency asturbines performed at head of water flow resource through the pumps as high as their maximum characteristic head of thepumps. Furthermore, both pumps as turbines generate high shaft revolution that was about 1.500 rpm at their maximumefficiency. Although those efficiencies are considerably low to an ideal efficiency 100%, however, the volute-pump as turbineperforms a reasonably efficiency (32%) that higher than (at least is same as) the efficiency of its pump characteristic (26%),and this pump available very widely in the market. Should be pointed out that bigger dimension pumps propose higherefficiency up to about 86%, therefore they are expected to give higher efficiency as well. So, centrifugal volute-pumps arepotential alternative solution to be used as hydro turbines.
Keywords: Pump, Hydro turbins, Reverse pump, Pump as turbine